Pengaruh Tingkat Pelapukan Terhadap Distribusi Ukuran Butir Pada Sampel Tanah Limonit dan Saprolit di Lokasi Penambangan Bijih Nikel Kecamatan Lasolo - Aqsal Ramadhan S.; La Ode Dzakir (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2022)
The level of weathering in nickel ore deposits greatly affects the grain size distribution of the soil material, so a study was conducted to determine the effect of weathering on the grain size distribution of limonite and saprolite soil materials. Based on the results of the research conducted, it is known that the limonite zone has a percentage of 0.00% gravel, 84.33% sand and 15.67% silt/clay. While the saprolite zone has a percentage of 14.20% gravel, 75.80% sand and 10.01% silt/clay. Thus it can be concluded that the level of weathering greatly affects the distribution of grain size on the soil material, where the higher the level of weathering of a material, the finer/smaller the grain size.